Questionnaire For Diagnosing the Emotional Component of Essential Self-Regulation (QDES-2-E) and its Interpretation - Kocharian, Igor (Psychological Counseling and Psychotherapy, 2025)
The article presents the author-developed psychodiagnostic method – “Questionnaire for Diagnosing the Emotional Component of Essential Self-Regulation (QDES-2-E)”, designed to study the emotional dimension of essential self-regulation in personality. The concept of essential self-regulation is understood as an individual's ability to realize their inherent tendency toward self-actualization, maintain authenticity, inner coherence, and a sense of meaning in various life circumstances, relying not only on functional control mechanisms but primarily on the connection with personal values, deep needs, and essential identity. This approach is relevant in the context of studying personal growth, self-realization, overcoming existential crises, and preserving psychological well-being. The method allows the exploration of four types of emotional states: affect (intense, often impulsive arousal), ambivalence (emotional contradiction, inner conflict), optimum (a state of balance, harmony, integration), and apathy (lack of emotional involvement, detachment). Each of these modes is assessed across three key areas of functioning: general (existential), professional, and family. The test consists of 6 situational blocks that simulate typical life challenges; each block contains 8 response options. Respondents select from 3 to 5 options that best reflect their emotional reactions. This format allows for the registration of the multidimensionality of emotional experience and the identification of an individual self-regulation profile. The method is applicable in scientific research, psychotherapeutic and counseling practice, educational settings, and psychological support of personal development. The article presents the theoretical foundations of the method, its structure, scale design principles, logic of result interpretation, and practical applications for identifying personal strengths, vulnerabilities, and the potential for emotional integration.